Interspecies variation in DNA damage induced by pollution. Issue 2 (1st April 2014) - Sebbio, Claudia; Carere, Claudio; Nascetti, Giuseppe; Bellisario, Bruno; Mosesso, Pasquale; Cimmaruta, Roberta; Angeletti, Dario
Abstract: The choice of a suitable species to translate pollution signals into a quantitative monitor is a fundamental step in biomonitoring plans. Here we present the results of three years of biomonitoring at a new coal power plant in central Italy using three different aquatic and terrestrial wildlife species in order to compare their reliability as sentinel organisms for genotoxicity. The comet assay was applied to the common land snail Helix spp ., the lagoon fish Aphanius fasciatus, and the green frog Rana esculenta sampled in the area potentially exposed to the impact of the power station. The tissue concentration of some expected pollutants (As, Cd, Ni, Pb, Cr) was analysed in parallel samples collected in the same sampling sites. The three species showed different values in the comet assay (Tail Intensity) and different accumulation profiles of heavy metals. Aphanius fasciatus showed an increasing genotoxic effect over time that paralleled the temporal increase of the heavy metals, especially arsenic, and the highest correlation between heavy metals and DNA damage. Helix spp. showed levels of damage inversely related to the distance from the source of pollution and in partial accordance with the total accumulation of trace elements. On the contrary, Rana esculenta showed a low capability to accumulate metals and had inconsistent results in the comet test. The fish appeared to be the most efficient and sensitive species in detecting chemical pollution. Overall, both the fish and the snail reflected a trend of increasing pollution in the area surrounding the power plant across time and space.